Glob all Mix - Glob all Mix (2012)
This initiative, inspired by the central themes of the conference, stimulates creativity and helps translate complex concepts into powerful and striking messages. The messages convened by Rio+20 are important, and deserve to be communicated by the most talented artists in the field of graphic design